Evolocumab treatment is associated with early and sustained reductions in low-density cholesterol (LDL-C) over 30 months: final results from the pan-European observational HEYMANS registry. (3rd October 2022) - Ray, K K; Perrone-Filardi, P; Ebenbichler, C; Vogt, A; Bridges, I; Sibartie, M; Dhalwani, N N
Abstract: Background: Variability in LDL-C control at a population level associates with worse CV outcomes. This could in part be related to variations in patient adherence to self-administration regimens or variability in the response to a given therapy. Potent therapies such as PCSK9 inhibitors (PCSK9i) reduce cardiovascular events but some have questioned whether these therapies, which require dosing every 2 weeks, can offer sustained population level control of LDL-C. Purpose: Using data from the HEYMANS registry, the objective of these analyses was to evaluate, at a population level, various metrics of variability in LDL-C reduction over time with evolocumab treatment. Methods: HEYMANS was a prospective registry including adults initiating evolocumab treatment in clinical practice in 12 European countries between August 2015 to June 2020. Patient data were collected for ≤6 months before evolocumab initiation (baseline) and ≤30 months post initiation. LDL-C measurements were collected per clinical practice. At each 3-month time point in the study, we analysed median (and 95% CI) reductions in LDL-C, and the proportion of patients achieving ≥30% and ≥50% reductions in LDL-C from baseline. Results: Data from 1951 patients were included in this final analysis (62% male, mean age 60 years, median baseline LDL-C 3.98 [Q1–Q3 3.17–5.07]) mmol/L). Most patients (85%) were receiving evolocumab for secondary prevention, with 40% not on oral LLT of whom the majority reported a history of statin intolerance. There was a median of 4 (Q1, Q3: 2, 6) LDL-C measurements per patient during follow-up. Within 3 months of initiating evolocumab treatment, LDL-C levels had reduced by a median of 58% and this reduction was maintained over 30 months (Figure 1). Among patients with an LDL-C value, ∼85% achieved a ≥30% reduction at each follow-up throughout the study, and ∼63% achieved a ≥50% reduction at each visit (Figure 2). Conclusions: In European clinical practice, evolocumab treatment was associated with early and sustained reductions in LDL-C of over 30 months, with limited variability in LDL-C reductions at a population level. Within 3 months of treatment, evolocumab was associated with ∼58% reduction in LDL-C levels that was maintained throughout the study. These data should reassure the clinical community that meaningful, consistent additional reductions in LDL-C can be achieved with use of evolocumab. As greater use of combination therapies is required to achieve lower LDL-C goals, expanding the use of PCSK9i could provide improvements in population level control of LDL-C in European clinical practice. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen (Europe) GmbH